Exploring a bioneurofeedback training intervention to enhance psychological skills & performance in sport - Dupee, Margaret (University of Ottawa (Canada), 2008)
The purpose of the present study was to explore whether BNFK, which trains self-awareness and self-regulation of physiological and mental-emotional states, can enhance an athlete's psychological skills, specifically their ability to focus, relax and regulate their arousal and anxiety levels, and ultimately, enhance their sport performance. This research utilized a multiple-case study design. Six elite athletes, with a minimum of five years experience at the international or Olympic level, each received 30 hours of a BNFK training intervention. The effect of BNFK training was explored in three ways: (a) three phases of interviews were conducted with each athlete, prior to the BNFK training, between 20-30 hours of BNFK training, and at the end of the 2007-2008 competitive season; (b) physiological and neurological quantitative data was collected which measured improvements specific to the BNFK training; and (c) performance results were noted at the completion of the 2007-2008 competitive season and compared to previous results. The findings indicate that within the lab setting, the athletes developed (i) greater self-awareness of how they hold tension and anxiety in the body and (ii) self-regulation techniques to decrease that tension. As well, the athletes became more aware of their mental state, and through regulation of their level of anxiety and tension in the body, they enhanced their ability to focus. Although much improvement was seen, none of the athletes developed optimal self-regulation of all aspects measured. With respect to competition results, no definite improvement in performance was seen. The results of the study are further discussed in the context of the BNFK and sport psychology literature. Implications and future directions are also offered.
Keywords: Health Sciences, Recreation.